(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Some observations carried out by scanning electron microscopy on the functional complex resulting from the «Eltringham organ» (pilula axillaris) and from the related lateral modifications of the lst tergite in the antlion Euroleon nostras (Fourcroy) are given. As for the lst tergite, morphological details of the dorsal edge of lateral pit are pointed out, and its fine structure is illustrated for the first time in high magnification (it is made up of a row of lamellar teeth). Both hypotheses hitherto suggested by the Authors about the function of the complex, present only in males and probably involved in communication (either chemical or acoustic) between the sexes during courtship or mating, are recorded and discussed briefly.